A critical review of methods for decontaminating filtering facepiece respirators. (September 2020) - Jacobs, Neva; Chan, Kathy; Leso, Veruscka; D'Anna, Andrea; Hollins, Dana; Iavicoli, Ivo
Various decontamination methods that may be used to extend respirator inventories have been examined for over a decade. In light of the ongoing coronavirus disease 2019 pandemic, many health-care settings are now implementing these techniques amid respirator shortages. We sought to perform a critical review of the available literature regarding decontamination methods to determine which strategies are effective at inactivating the target organism, preserve performance (filter efficiency and fit) of the respirator, leave no residual toxicity from the treatment, and are fast-acting, inexpensive, and readily available. We also identified areas for future research. We found that ultraviolet germicidal irradiation (UVGI) is the most widely studied method, and treatments are effective at inactivating SARS-CoV-2 without diminishing filtration efficiency or fit. These treatments were found to leave no residual toxicity for the wearer, have a relatively short cycle time of less than 1 h, and existing systems can likely be retrofitted to accommodate this method. Further, UVGI (among other treatment methods) has been recommended by the Centers for Disease Control and Prevention (CDC), Occupational Safety and Health Administration (OSHA), and respirator manufacturers. Methods involving microwave-generated steam also show potential in that they are likely effective against SARS-CoV-2, preserve performance, have no residual toxicity, require a short duration treatment cycle (often less than 10 min), and microwave ovens are inexpensive and readily available. Steam methods are currently recommended by the CDC, OSHA, and manufacturers. These respirator decontamination methods are likely also useful against other viruses or pathogens.